Revitalisasi koridor komersial bersejarah Jalan Surabaya dengan konsep retrofitting di Kota Medan - Affif, Aulia Malik; Hadinugroho, Dwi Lindarto (EMARA: Indonesian Journal of Architecture, 2020)
Jalan Surabaya has been known as a watch-selling district and a Chinatown residential area that, in the Dutch era, was called the Canton Straat. Along with the development of the era of Jalan Surabaya, the visual quality degrades with the historical value attached to it. This research aims to produce the concept of revitalizing the historic area of ​​Jalan Surabaya with a retrofitting approach. A qualitative descriptive method used in the research with the stage begins by analyzing various aspects of the area, including physical, social, economic, and cultural aspects. Three main retrofitting strategies are used to produce a regional revitalization model. The results show that the Jalan Surabaya area's revitalization can be achieved by constructing a Chinatown gate, public open space, public transport infrastructure, signage, parking area, pedestrian arrangement, and historic buildings conservation. For the revitalization model to be implemented, it will require all parties' support, including local community participation.